EFFECTIVENESS OF MUROTTAL AL-QUR'AN THERAPY AND MASSAGE THERAPY ON THE DECREASE IN THE PAIN SCALE OF BREASTFALL I ACTIVE PHASE OF BIRTH IN PMB Bd.MULIANA, S.Tr.Keb., M.Keb. AND PMB EVA YANTI, SST ACEH BESAR DISTRICT - Ummu Aiman; Muliana Muliana (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Pain during labor is a physiological condition, but if left untreated pain can affect the mother's condition in the form of fatigue, fear of worry and stress that will increase pain. The purpose of this study was to determine the effectiveness of Qur'anic Murottal Therapy and Massage Therapy on reducing the pain scale of labor phase I active phase of laboring mothers at PMB Bd.Muliana, S.Tr.Keb., M.KM and PMB Eva Yanti, SST. Aceh Besar Regency. This type of research is quantitative with a Quasy Experiment Pre and Post two group approach. The sample of this study was 60 respondents from the total population of all laboring mothers who were divided into 2 groups, namely 30 respondents who were given Al-Qur'an Murottal Therapy and 30 respondents who were given Massage Therapy. The sampling technique in this study using consecutive sampling technique. The results of statistical tests used in this study are Wilcoxon test. Both groups experienced an increase after doing Al-Qur'an Murottal Therapy and Massage Therapy, the P value of the two groups was 0.00, and the comparative value of Al-Qur'an Murottal Therapy and Massae Therapy using the Man Withney U test p value. The value of Al-Qur'an Murottal Therapy is 37.40 and Massage Therapy is 23.60, which means Massage Therapy is more effective than Al-Qur'an Murottal therapy.